2002
DOI: 10.1002/1099-0690(200211)2002:22<3734::aid-ejoc3734>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Uncatalyzed Baeyer−Villiger Oxidation of Cyclobutanones to γ-Lactones by Air and Its Mechanistic Implications

Abstract: The cyclobutanone moieties in 5-aryl-7,11,11-trimethyltricyclo[5.4.0.0 3,6 ]undec-1-en-4-ones 4a−e undergo an unusual, uncatalyzed Baeyer−Villiger (BV) oxidation when their methanolic solutions are exposed to air at room temperature for 45 d, quantitatively producing mixtures of γ-lactones (5a−e, 6a−e); the ratio 5/6 varies with the nature of the substituent on the aryl ring (9:1 to ca. 1:1). BV oxidations of 4a−c and 4e with H 2 O 2 and of 4c−d with performic acid have also been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Considering that two different regioisomeric c-butyrolactones could have been obtained, the chemical shifts for the methylenic carbon atoms confirmed that the reaction proceeds by a Baeyer-Villiger-like (BV) rearrangement [26] rendering 3a or 3b as a sole product. Little is known about the BV oxidation of cyclic ketones to lactones by hypochlorous acid.…”
Section: Oxidation Conditions Of Cyclobutanols 2395mentioning
confidence: 99%
“…Considering that two different regioisomeric c-butyrolactones could have been obtained, the chemical shifts for the methylenic carbon atoms confirmed that the reaction proceeds by a Baeyer-Villiger-like (BV) rearrangement [26] rendering 3a or 3b as a sole product. Little is known about the BV oxidation of cyclic ketones to lactones by hypochlorous acid.…”
Section: Oxidation Conditions Of Cyclobutanols 2395mentioning
confidence: 99%